An unfolded protein response (UPR)-signature regulated by the NFKB–miR-29b/c axis fosters tumor aggressiveness and poor survival in bladder cancer - Zhang, Jian; Fan, Xiaosong; Chen, Yu; Han, Yichao; Yu, Weixing; Zhang, Shaolin; Yang, Bicheng; Zhang, Junlong; Chen, Yanling (Frontiers in Molecular Biosciences, 2025)
BackgroundBladder cancer continues to pose a substantial global health challenge, marked by a high mortality rate despite advances in treatment options. Therefore, in-depth understanding of molecular mechanisms related to disease onset, progression, and patient survival is of utmost importance in bladder cancer research. Here, we aimed to investigate the underlying mechanisms using a stringent differential expression and survival analyses-based pipeline.MethodsGene and miRNA expression data from TCGA and NCBI GEO databases were analyzed. Differentially expressed genes between normal vs tumor, among tumor aggressiveness groups and between early vs advanced stage were identified using Student's t-test and ANOVA. Kaplan-Meier survival analyses were conducted using R. Functional annotation, miRNA target and transcription factor prediction, network construction, random walk analysis and gene set enrichment analyses were performed using DAVID, miRDIP, TransmiR, Cytoscape, Java and GSEA respectively.ResultsWe identified elevated endoplasmic reticulum (ER) stress response as key culprit, as an eight-gene unfolded protein response (UPR)-related gene signature (UPR-GS) drives aggressive disease and poor survival in bladder cancer patients. This elevated UPR-GS is linked to the downregulation of two miRNAs from the miR-29 family (miR-29b-2-5p and miR-29c-5p), which can limit UPR-driven tumor aggressiveness and improve patient survival. At further upstream, the inflammation-related NFKB transcription factor inhibits miR-29b/c expression, driving UPR-related tumor progression and determining poor survival in bladder cancer patients.ConclusionThese findings highlight that the aberrantly activated UPR, regulated by the NFKB-miR-29b/c axis, plays a crucial role in tumor aggressiveness and disease progression in bladder cancer, highlighting potential targets for therapeutic interventions and prognostic markers in bladder cancer management.